Exact Traveling Wave Solutions to Benney- Luke Equation - Islam, Zahidul; Hossain, Mohammad Mobarak; Sheikh, Md Abu Naim (GANIT: Journal of Bangladesh Mathematical Society, 2018)
By using the improved (G¢/G) -expansion method, we obtained some travelling wave solutions of well-known nonlinear Sobolev type partial differential equations, namely, the Benney-Luke equation. We show that the improved (G¢/G) -expansion method is a useful, reliable, and concise method to solve these types of equations. GANIT J. Bangladesh Math. Soc.Vol. 37 (2017) 1-14